FRI0046 Identification of HERV-K env surface peptides highly recognized in ra patients. (15th June 2017) - Erre, GL; Mameli, G; Cossu, D; Mura, S; Piras, A; Cadoni, ML; Buscetta, G; Mundula, N; Colombo, E; Longu, MG; Sechi, LA; Passiu, G
Abstract : Background: Endogenous Retroviruses (HERV) are believed to be pathogenic in several autoimmune diseases. Among them, HERV-K viruses have been recently reported to be involved in the pathogenesis of rheumatoid arthritis (RA). Objectives: In this study we have explored the role of humoral immune response against HERV-K as a potential pathogenetic mechanism in RA. Methods: Four different peptides from the extracellular portion of the env protein of HERV-K (env-su 19–37, env-su 109–26, env-su 164–205, env-su 209–226 ) were selected by bioinformatic analysis on the basis of their putative immunogenicity. Indirect ELISA was then carried out to quantify antibodies against those peptides on blood samples from RA patients and healthy controls (HC). Differences between the two groups were analysed using the Mann-Whitney rank-sum and chi-square tests. Potential correlations between RA laboratory, clinical descriptors and IgGs levels were explored by bivariate regression analysis. Results: Seventy consecutive RA patients and seventy-one HC crossed by age and sex were enrolled in the study. Serum autoantibodies against three out of the four tested peptides, anti HERV-Ksu19–37, HERV-K env-su109–126 and HERV-K env-su205–226, were significantly more prevalent in RA than in HC (19% vs 3%, p=0.0001;9% vs 3%, p=0.0001; and 6% vs 3%, p=0.0001 respectively) (See Fig. 1 ) Subgroup analysis showed no association between anti-HERV-K peptide humoral response and clinical, serological and clinimetric RA disease descriptors. Conclusions: Serum from RA patients in our series significantly reacted against different HERV-K peptides in comparison to the general population suggesting a role for the HERV-K related, secondary antigenic driven immune response in the pathogenesis of RA. Further studies are needed to confirm these results and to explore the role of HERV-K surface peptides as potential therapeutic targets. Disclosure of Interest: None declared